The fields of the eschatological lexicon in children’s black humor - Jiménez Ruiz, Juan Luis (Círculo de Lingüística Aplicada a la Comunicación, 2023)
This study explores the inferential linguistic processes which underlie the phenomenon of black humour –or humour in bad taste– in a population of children. To this end, and based on the findings of the Project “Metapragmática del humor infantil: adquisición, perspectiva de género y aplicaciones” (Metapragmatics of children’s humour: acquisition, gender perspective and applications) (GRE 14-19, University of Alicante), we will focus on the linguistic devices used by children aged between 8 and 12 years to express black humour in their language production, looking specifically at the use of the scatological lexicon in this context.
Keywords: children’s black humour; metapragmatics; metapragmaticsfigurativity; scatological lexicon